Class IV composite restorations of central Incisors: One-shade vs multishade, case series - DOĞU, BENGÜ; TARÇIN, BİLGE; YILMAZ ATALI, PINAR (My University, 2022)
Aim: Fractures or deformities are common in central incisors. The aim of this case series was to compare and evaluate incisal/class IV restorations using 3 different composites: OptiShade (Kerr), Amaris (Voco), and Ceram-X Duo (Dentpsly-Sirona). Case Description: 3 patients with the complaint of fractures on their anterior teeth were applied to the clinics of Restorative Dentistry Department (Case1 18-year-old female, Case 2 20-year-old female, and Case 3 17-yearold male). Following radiographic and clinical examinations, enamel fracture was detected in the incisal 1/3 of the central incisors and it was decided to perform direct composite resin restorations (CRR) as the treatment plan. 37% orthophosphoric acid (Kerr) was used in selective-etch mode. 3 different universal adhesive agents (OptiBond Universal, Kerr; Futurabond U, Voco; and Prime&Bond Universal, Dentsply-Sirona) were applied to the cavities according to manufacturer’s instructions. CRRs were completed with nano-hybrid (Amaris TL and D2, Voco), one-shade (OptiShade Light and Medium, Kerr), and ceramic reinforced (Ceram-X Duo D2 and E1, Denstply-Sirona) composites using incremental technique. Valo-Cordless (Ultradent) was used for polimerisation with 1000 mW/cm2. Finishing and polishing procedures were performed with polishing discs (Bisco) and Twist Dia (Kuraray) polishing wheels. Patients were recalled at 1 and 3-months for clinical evaluation and scores according to FDI criteria. Results: The esthetic, functional and biological evaluation of the restorations according to the FDI criteria in 1 and 3-months follow-up were scored as 1. Discussion: One shade universal composite provide advantage in color selection for the clinician, however composites with different contents and brands vary in opacity, color, and brightness. Considering the esthetic expectation of the patients and the longevity of class IV CRR, the material should be selected considering the shape, color and fracture line of the tooth structure and the optic properties of the material.
Keywords: one-shade composite resins; incremental technique; class iv restoration